Postmodern Analysis of Southeast Asian Identities - Lanuza, Gerardo M. (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 2 (2000): Indigenous Peoples, 2009)
A book review of Joel Kahn's "Southeast Asian Identities: Culture and the Politics of Representation in Indonesia, Malaysia and Thailand"